Hubungan Kebiasaan Menonton Mukbang terhadap Nafsu Makan, Pola Makan dan Status Gizi Mahasiswa di Jakarta: The Relationship Between Mukbang Viewing Habits Between Eating Appetite, Eating Patterns, And Nutritional Status Of Students In Jakarta - Erna Thania; Wardina Humayrah (Universitas Ngudi Waluyo, 2023)
ABSTRACT Watching mukbang videos is a habit that has become a trend, especially among teenagers and adults. Supported by easy internet access and unlimited types of mukbang videos on social media, it is one of the factors for the spread of mukbang fans, especially among students. The display of food and eating activities presented in the mukbang video triggers a visual stimulus that can stimulate the desire to eat for the audience. In general, the food shown in mukbang videos tends not to pay attention to nutritional content, higher in calories, fat, sugar, and sodium. This study aims to analyze the relationship between watching mukbang habits with appetite, diet, and nutritional status in students who regularly watch mukbang. The design of this study is cross-sectional with the subject of 85 regular students outside the Nutrition Study Program at Sahid University who are included in the routine category of watching mukbang. Data analysis using the Spearman Rank correlation test. For most of the subjects, watching with a moderate duration (240-479 minutes/week) was 51.8%. There was no significant association (p>0.05) between mukbang viewing habits and eating desires, diet, and nutritional status. There is a possibility that watching mukbang is an indirect factor that can affect students' appetite, diet, and nutritional status. Some of the contributing factors that may be found include genetics, sleep duration, physical activity, health problems, psychological, body and mage preferences, family income, and parental education. Keywords: Mukbang, appetite, diet, nutritional status ABSTRAK Menonton video mukbang merupakan kebiasaan yang menjadi tren hingga saat ini terutama pada kalangan remaja dan dewasa. Ditunjang dengan akses internet yang mudah dan jenis video mukbang yang tidak terbatas di media sosial menjadi salah satu faktor tersebarnya penggemar mukbang terutama pada kalangan mahasiswa. Tampilan makanan dan kegiatan makan yang dibawakan dalam video mukbang memicu stimulus visual sehingga dapat merangsang keinginan makan terhadap penonton. Secara umum, makanan yang ditampilkan pada video mukbang cenderung tidak memerhatikan kandungan gizi, lebih tinggi kalori, lemak, gula dan natrium. Penelitian ini bertujuan untuk menganalisis hubungan kebiasaan menonton mukbang dengan nafsu makan, pola makan, dan status gizi pada mahasiswa yang rutin menonton mukbang. Desain penelitian ini adalah cross sectional dengan subjek sebanyak 85 mahasiswa reguler di luar Program Studi Gizi di Universitas Sahid yang masuk dalam kategori rutin menonton mukbang. Analisis data menggunakan uji korelasi Rank Spearman. Sebagian besar subjek, menonton dengan durasi sedang (240-479 menit/minggu) sebanyak 51,8%. Tidak ada hubungan yang signifikan (p>0,05) antara kebiasaan menonton mukbang dengan keinginan makan, pola makan, dan status gizi. Terdapat kemungkinan menonton mukbang merupakan faktor tidak langsung yang dapat memengaruhi nafsu makan, pola makan dan status gizi mahasiswa. Beberapa faktor perancu yang mungkin ditemukan antara lain, genetik, durasi tidur, aktivitas fisik, masalah kesehatan, psikologis, preferensi body image, pendapatan keluarga, dan pendidikan orang tua. Kata kunci: Mukbang, nafsu makan, pola makan, status gizi